THE CIA AND THE US DIPLOMACY IN COSTA RICA: JOSE FIGUERES, ‘ANTI-AMERICANISM’ AND THE DECENTERED COLD WAR, 1968-1973 - Ugalde Barrantes, Daniel (2025)
This article analyzes the perceptions that the CIA and the United States Department of State had of the National Liberation Party and its main leader at the beginning of the 1970s: José Figueres Ferrer. The study is based on the declassified files from both instances of the U.S. government. The proposed analysis is carried out from a decentered perspective, which allows for a rethinking of the global dynamics of the Cold War from the agency and the conditions of possibility of Costa Rican actors in a scenario of political and ideological pressures. The article concludes that the perceptions of U.S. officials about Costa Rican politics can be explained by the autonomy gained by Latin American actors during the détente period.